RNA pseudoknots and the regulation of protein synthesis. - Brierley, I; Gilbert, R; Pennell, S (2008)
RNA pseudoknots are structural elements found in almost all classes of RNA. Pseudoknots form when a single-stranded region in the loop of a hairpin base-pairs with a stretch of complementary nucleotides elsewhere in the RNA chain. This simple folding strategy is capable of generating a large number of stable three-dimensional folds that display a diverse range of highly specific functions in a variety of biological processes. The present review focuses on pseudoknots that act in the regulation of protein synthesis using cellular and viral examples to illustrate their versatility. Emphasis is placed on structurally well-defined pseudoknots that play a role in internal ribosome entry, autoregulation of initiation, ribosomal frameshifting during elongation and trans-translation.